Aberrant Expression of Long Non-coding RNAs in Exosomes in Follicle Fluid From PCOS Patients - Wang, Liping; Fan, Hairui; Zou, Yinggang; Yuan, Qiuyue; Hu, Xuming; Chen, Xujing; Zhu, Chunhui; Zhang, Xiaomei; Cui, Hengmi (Frontiers in Genetics, 2021)
Polycystic ovary syndrome (PCOS) is a common reproductive endocrine disease characterized by persistent anovulation and hyperandrogenism, affecting approximately 8%-10% of women of childbearing age and occupying an important position in the etiology of infertility. There is increasing evidence that lncRNAs are involved in the development of PCOS, but the potential regulatory mechanism is still unclear. This study performed high-throughput lncRNA sequencing of follicular fluid exosomes in non-PCOS infertility patients and PCOS infertility patients. The sequencing results led to the identification of 1253 upregulated and 613 downregulated lncRNAs from a total of 1866 detected candidates. There was no significant difference between the PCOS patients and non-PCOS patients in body mass index (BMI) or the fasting blood glucose (FBG) level. However, luteinizing hormone (LH), estradiol (E2), testosterone (T), serum prolactin (PRL) and anti-Mullerian hormone (AMH) levels were clearly upregulated in PCOS patients compared to those in non-PCOS patients. There was also an increase in LH/FSH (>2) in the PCOS patients. Functional analysis showed that the functions of lncRNAs were related to adenine metabolism, adenine biosynthesis and cytidine triphosphate biosynthesis. These results suggest that lncRNAs may play an important role in the pathogenesis of PCOS and may be potential targets for the diagnosis and treatment of PCOS.